Modeling of corrosion process of the high-performance concretes in sulfate environment - Sheinich, Leonid; Pryymachenko, Artem (Eastern-European Journal of Enterprise Technologies, 2016)
The main contemporary method for measuring stability of concrete in aggressive environments is to compare the strength of concrete that solidified in an aggressive environment with the strength of concrete that solidified in a non-aggressive environment. This approach to testing has been quite effective in many cases, but it does not allow analysing the impact of corrosion products on the strength of concrete cement matrix. Such data can be obtained after removing corrosion products from the cement matrix of concrete. The techniques applied in the study involved removal of corrosion products while subjecting the samples to aggressive environments, which helped determine that a cement skeleton of concrete with an integrated active mineral additive (a mixture of acidic ash removal of metakaolin in optimal quantities) has greater strength and corrosion resistance than a cement skeleton of concrete without a complex active mineral additive. A combination of physical and chemical methods of research – such as phase-contrast X-ray imaging, thermal, and electron microscopy – showed that a complex active mineral additive produces cement structure peculiarities. Thus, it has been determined that frames with a complex active mineral additive can form dense structures with a significant number of low-base calcium silicate hydrates and solid solutions of hydrated aluminium silicate composition (hydrated galena – hydrated anorthite). This is quite different from structures without the complex active mineral additive, which are characterized in an aggressive environment (for example, in a solution of sulphuric acid) by leaching of soluble compounds such as portlandite; moreover, this process is intensified by smoothing the sample surface. These peculiarities of forming cement matrix structure explain the high corrosion resistance of concretes. The obtained data are important for developing a composition of concretes for reinforced concrete structures that are used in aggressive environments.